Developing Earth Science Modules For The Secondary School - Krockover, Gerald H. (Journal of geological education, 1977)
This article is designed to provide secondary earth science teachers with a readily available source of information for developing their own instructional modules. In addition to providing the teacher with sources of materials for modular development, the article introduces the teacher to the individualized earth science module and the components of a module. A sample instructional module for use in secondary earth science classes is also included.